METAPHORICAL STRUCTURES IN ADVERTISING SLOGANS: A STYLISTIC AND COGNITIVE APPROACH - Egamberdiyeva Yulduzxon Muhammadjon qizi (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This article explores the stylistic features and cognitive functions of metaphorical structures in advertising slogans. Based on an analysis of 200 advertising slogans, the study categorizes metaphors into four types—personification, journey, war/conflict, and nature/elemental metaphors—and evaluates their frequency and function. Drawing on Conceptual Metaphor Theory and Blending Theory, the research highlights how metaphors enhance emotional engagement, shape consumer perception, and reinforce brand identity. The findings demonstrate that different industries strategically use metaphor types to align with consumer expectations and marketing goals.